An introduction to habitat use and selection by waterfowl in the northern hemisphere - Kaminski, Rick M.; Elmberg, Johan (Wildfowl, 2014)
This introductory article aims to provide a theoretical framework to the topics of habitat use and selection by waterfowl (i.e. family Anatidae) in the northern hemisphere during the four stages of their annual cycle: autumn migration and winter, spring migration and pre-breeding, nesting and brood rearing, and postbreedingÂ and moulting. Papers addressing each of these seasonal sectors of theÂ annual cycle, which follow this introduction, were presented at the 6th North American Duck Symposium, â€œEcology and Conservation of North American Waterfowlâ€ in Memphis, Tennessee in January 2013. Here, we consider the theoryÂ and selected empirical evidence relevant to waterfowl habitat and resource use andÂ selection that may affect individual survival and fitness of waterfowl in Nearctic andÂ Palearctic ecozones. Additionally, where possible, a comparative taxonomic approachÂ is attempted in the following papers to identify and generalise patterns in habitat andÂ resource use and selection across waterfowl taxa that may influence biologicalÂ outcomes for individuals, populations and species through space and time. Each ofÂ the subsequent papers use accumulated science-based information to recommendÂ future opportunities and strategies for research and for habitat and populationÂ conservation. Collectively, our goals in synthesising information on waterfowl are toÂ help sustain harvestable populations of waterfowl and to protect rare species amidÂ worldwide changes in climate, landscape, economics, socio-politics and growth ofÂ human populations.